Chronic Closed Transection of the Biceps Brachii: A Case Report - A Pandit; A Wang; S McKay; T Ackland (Journal of Orthopaedic Surgery, 2011)
A 32-year-old man presented with chronic closed transection of the biceps brachii of the right arm after 30 months of conservative treatment. Magnetic resonance imaging showed atrophy of both long and short heads of the biceps brachii, with a 5-cm defect secondary to proximal and distal retraction on either side of the tear. There was a similar defect in the coracobrachialis, but the triceps brachii was normal. The self-rated overall arm status was 4 out of 10 (using a visual analogue scale). Objective functional deficit was measured using a dynamometer. Forearm flexion and supination strength of each arm at 120°/s was tested. The patient had a 34% deficit (40 vs. 61 Nm) in peak torque during forearm flexion and a 22% deficit (10 vs. 12 Nm) during forearm supination. The patient could not maintain maximal torque throughout the range of motion, with an approximately 50% deficit in the later part of the range of motion. The patient underwent reconstruction of the biceps brachii using an interposition Achilles tendon allograft.